Structural Properties and Crystallization Behavior of FINEMET Fe74Cu1.5Nb2.5Si12B10 Alloy Under Different Annealing Condition (Dhaka University Journal of Science, 2016)
The effect of annealing condition on nanocrystalline amorphous FINEMET type of alloy with nominal composition Fe74Cu1.5Nb2.5Si12B10 prepared by rapid solidification method has been studied to observe the structural properties and crystallization behavior of the material. Nanocrystalline alloy with ferromagnetic bcc nanocrystals with size 15-29 nm embedded in a residual amorphous matrix was produced from amorphous precursor by appropriate annealing condition. The amorphosity of the material, primary crystallization temperature, the nanometric grain size, Si content and the lattice parameter of Fe(Si) nano-phase have been determined from XRD patterns of the samples annealed at different temperatures ranging from 475°C - 650°C with annealing time 5, 12, 20 and 30 minutes. The annealing temperature 475°C (with annealing time of 12 minutes) was determined as primary crystallization temperature with grain size 15 nm, Si content 16.25 at.% and lattice parameter 2.8431 Å. The grains were found to grow rapidly after 550°C attaining a maximum value of 29 nm at the annealing temperature of 650°C. The grain size and Si content increase whereas the lattice parameter decreases with the increase of annealing temperature and time.Dhaka Univ. J. Sci. 64(1): 71-75, 2016 (January)